Identification of AtHsp90.6 involved in early embryogenesis and its structure prediction by molecular dynamics simulations - Luo, An (R Soc Open Sci, 2019)
Heat-shock protein of 90 kDa (Hsp90) is a key molecular chaperone involved in folding the synthesized protein and controlling protein quality. Conformational dynamics coupled to ATPase activity in N-terminal domain is essential for Hsp90's function. However, the relevant process is still largely unknown in plant Hsp90s, especially those required for plant embryogenesis which is inextricably tied up with human survival. Here, AtHsp90.6, a member of Hsp90 family in Arabidopsis, was firstly identified as a protein essential for embryogenesis. Thus we modelled AtHsp90.6 in its functionally closed ‘lid-down’ and open ‘lid-up’ states, exploring the nucleotide binding mechanism in these two states. Free energy landscape and electrostatic potential analysis revealed the switching mechanism between these two states. Collectively, this study quantitatively analysed the conformational changes of AtHsp90.6 bound to ATP or ADP. This result may help us understand the mechanism of action of AtHsp90.6 in future.